MILITARY-ECONOMIC ASPECTS OF MAINTAINING THE STATE'S DEFENCE CAPABILITY IN THE CURRENT MILITARY AND STRATEGIC SITUATION - Volodymyr Mozharovskyi; Serhii Hodz (Baltic Journal of Economic Studies, 2024)
The article outlines the content of one of the main military-economic aspects of maintaining Ukraine's defence capability in the current conditions of development of the military-strategic situation – mobilisation readiness and capabilities of the State, in particular, the capabilities of its defence-industrial complex to create new and modernise existing models of weapons and military equipment, and to produce missiles, ammunition and other material and technical means. Given the main contradictions in the development of the defence industry of Ukraine, the authors propose, as an option, a system of state management of the defence industry of Ukraine, which should be based on the centralisation of strategic functions for its development. In particular, it is proposed to create the State Agency for the Defence Industry of Ukraine – a structure with the status of a permanent executive body and broad powers to develop and implement the tasks of the defence industry. The paper focuses on the importance of protecting economic facilities, and the authors believe that one of the ways to improve the effectiveness of defending the country's economic potential is to create an additional echelon of non-fire protection for the most important economic facilities, such as energy infrastructure, industrial enterprises, ports, airfields, railway stations, etc. It is through the integrated use of active fire defence and passive non-fire defence means that the unconditional preservation of the country's economic potential can be achieved. At the same time, an analysis of the scientific literature in this area of research shows that existing methodologies (methodological approaches) do not provide for a comprehensive approach to substantiating ways to address the problematic issues of the state's defence capability, taking into account the main military and economic aspects of its maintenance, as well as the peculiarities of the development of the military-strategic situation. In view of this, the authors believe that the prospect of further research should be to reveal the content of other military-economic aspects of maintaining the state's defence capability in the current military-strategic situation, and, with this in mind, to develop a comprehensive methodological approach to substantiating ways to address the problematic issues of combat and mobilisation readiness of the Armed Forces and the Defence Forces of Ukraine as a whole. The analytical material presented in this article is based on the experience gained by the troops (forces) in the course of operations (combat actions).